Extended linear detection range for optical tweezers using a stop at the back focal plane of the condenser. (18th May 2015) - Mousavi, S Masoumeh; Samadi, Akbar; Hajizadeh, Faegheh; Reihani, S Nader S
Abstract: Optical tweezers are indispensable micro-manipulation tools. It is known that optical tweezers are force rather than position sensors due to the shorter linear range of their position detection system. In this paper, we have shown for the first time, that positioning an optical stop at the BFP of the condenser can overcome this problem by extending the linear detection range. This method would be valuable for the force spectroscopy applications of optical tweezers.